Anthropological characteristics of individuals of the IX–XI centuries from the monument of Dvin (Armenia) with growth disorders - Khudaverdyan A.Yu.; Hakopyan N.G.; Zhamkochyan А.S.; Engibaryan A.A.; Hovanisyan А.А. (Вестник археологии, антропологии и этнографии, 2017)
Irrespective of era and habitat, people paid more attention to extraordinary and unlike phenomena, than to everywhere found and usual ones. This article is about unusual individuals of the 9th–11th centuries from Dvin, among which traces of delay of growth processes were revealed. The paper analyzes individual features of craniological, cranioscopic, odontological, osteological and paleopathological characteristics of two individuals. Basing on a comprehensive anthropological study of finds, an attempt to reconstruct the way of life of the buried was made. Due to the lack of bones of the post-cranial skeleton of the individual No. 1, we can state only nanocephalia. Markers of an incidental stress (hypoplasia of enamel, cribra orbitalia) in this individual indicate systemic influence of negative factors, such as infections, frequent periods of starvation which interfered with normal development of the organism in the childhood. The skeleton No. 2 is characterized by the Laron-type dwarfism (Laron syndrome). The research of bones of the skeleton showed presence of serious pathologies, unrepresentative for so young age, related to excessive exercise stresses. An optional version of the activity is possible: the dwarf was a clown-acrobat. Harris lines, or growth arrest lines are clearly seen on Х-ray images of two diaphyses of tibial bones. Another marker of growth delays (enamel hypoplasia) is also found in the individual No. 2. Existence of one of the diet indicators (odontolith) and absence of caries indicate similarity of ingredients of the meals of two individuals, and tying, perhaps, proteinaceous origin of their food.